Genome architecture plasticity underlies DNA replication timing dynamics in cell differentiation - Yu, Wenjun; Zhong, Quan; Wen, Zi; Zhang, Weihan; Huang, Yanrong (Frontiers in Genetics, 2022)
During S-phase of eukaryotic cell cycle, DNA is replicated in a dedicatedly regulated temporal order, with regions containing active genes replicated early and those containing inactive genes replicated late. Recent sequencing technology advances allow us to explore connection between replication timing (RT), histone modifications and three-dimensional (3D) chromatin structure in diverse cell types. To characterize the dynamics during cell differentiation, corresponding se-quencing data for human embryonic stem cells (hESCs) and four differentiated cell types are collected. By comparing RT and its extent of conservation before and after germ layer specification, the human genome is partitioned into distinct categories. Each category is then subject to com-parisons on genomic, epigenetic and chromatin 3D structural features. As expected, while con-stitutive early and late replication regions show active and inactive features respectively, dynamic regions with switched RT possess intermediate features above mentioned. Surprisingly, although early-to-late replication and late-to-early replication regions possess similar histone modification patterns in hESCs, their structural preferences are opposite to default. Specifically, in hESCs ear-ly-to-late replication regions tend to be in B compartment and in large topologically associated domains, with late-to-early ones showing the opposites. Our results uncover the coordinated regulation of RT and 3D genome structure that underlies the loss of pluripotency and lineage commitment, and indicate the importance and potential roles of genome architecture in biological processes.